Redefining theatre communities : international perspectives on community-conscious theatre-making - Galea, Marco; Musca, Szabolcs (Intellect Books, 2019)
Redefining Theatre Communities explores the interplay between contemporary theatre and communities. It considers the aesthetic, social and cultural aspects of community-conscious theatre-making. It also reflects on transformations in structural, textual and theatrical conventions, and explores changing modes of production and spectatorship.